2013
DOI: 10.1002/pc.22582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solid lubricants on tribological behavior of glass fiber reinforced polyamide 6

Abstract: The tribological properties of glass fiber reinforced polyamide 6 (GF/PA6, 15/85 by weight) and its composites filled with solid lubricants were investigated. The main purposes of this article were to study the hybrid effect of solid lubricants with glass fiber as well as the synergism of combined solid lubricants, the wear mechanisms were studied by SEM. The results showed that graphite impaired the tribological properties of GF/PA6, but the tribology behavior of graphite filled GF/PA6 composite could be sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The possible mechanisms of selective adsorption [37], excluded free volume [38] and ball-bearing effect [39] are also reported in literature to explain the decrease in melt viscosity when nanofillers are introduced to the polymer matrix. Another possible explanation for observed melt viscosity changes with GO loading can result from lubricant behaviour of graphite [40]. The graphene layers coupled by week van der Waals-like bonds can easily slide past each other.…”
Section: Physical Properties Of Nanocompositesmentioning
confidence: 99%
“…The possible mechanisms of selective adsorption [37], excluded free volume [38] and ball-bearing effect [39] are also reported in literature to explain the decrease in melt viscosity when nanofillers are introduced to the polymer matrix. Another possible explanation for observed melt viscosity changes with GO loading can result from lubricant behaviour of graphite [40]. The graphene layers coupled by week van der Waals-like bonds can easily slide past each other.…”
Section: Physical Properties Of Nanocompositesmentioning
confidence: 99%
“…To obtain the desired properties of a PMC, the reinforcements and fillers are added to thermoset/thermoplastic matrices [35][36][37]. The synergistic improvements in mechanical and tribological properties in many cases are attained through the incorporation of glass or carbon fiber reinforcement and particulate fillers [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…The influence of different types of graphite on the properties of PA6, which is the subject of our work, was also studied; however, various results were reported. You et al reported that the addition of graphite (particle size 25 μm) to PA6/GF increased COF and wear [16]. In contrast, Unal and Mimaroglu found a decrease in COF and wear for PA6/graphite composites.…”
Section: Introductionmentioning
confidence: 99%